Experimental Study and Early Clinical Application Of a Sutureless Aortic Bioprosthesis - Walter J. Gomes; João Carlos Leal; Fabio Biscegli Jatene; Nelson A. Hossne Jr; Renata Gabaldi; Glaucia Basso Frazzato; Guilherme Agreli; Domingo M. Braile (Brazilian Journal of Cardiovascular Surgery, 2015)
ABSTRACT INTRODUCTION: The conventional aortic valve replacement is the treatment of choice for symptomatic severe aortic stenosis. Transcatheter technique is a viable alternative with promising results for inoperable patients. Sutureless bioprostheses have shown benefits in high-risk patients, such as reduction of aortic clamping and cardiopulmonary bypass, decreasing risks and adverse effects. OBJECTIVE: The objective of this study was to experimentally evaluate the implantation of a novel balloon-expandable aortic valve with sutureless bioprosthesis in sheep and report the early clinical application. METHODS: The bioprosthesis is made of a metal frame and bovine pericardium leaflets, encapsulated in a catheter. The animals underwent left thoracotomy and the cardiopulmonary bypass was established. The sutureless bioprosthesis was deployed to the aortic valve, with 1/3 of the structure on the left ventricular face. Cardiopulmonary bypass, aortic clamping and deployment times were recorded. Echocardiograms were performed before, during and after the surgery. The bioprosthesis was initially implanted in an 85 year-old patient with aortic stenosis and high risk for conventional surgery, EuroSCORE 40 and multiple comorbidities. RESULTS: The sutureless bioprosthesis was rapidly deployed (50-170 seconds; average=95 seconds). The aortic clamping time ranged from 6-10 minutes, average of 7 minutes; the mean cardiopulmonary bypass time was 71 minutes. Bioprostheses were properly positioned without perivalvar leak. In the first operated patient the aortic clamp time was 39 minutes and the patient had good postoperative course. CONCLUSION: The deployment of the sutureless bioprosthesis was safe and effective, thereby representing a new alternative to conventional surgery or transcatheter in moderate- to high-risk patients with severe aortic stenosis.